Geophysical investigations in the January 26, 2001 Bhuj earthquake affected region - Arora, B. R. (My University, 2001)
Number of geophysical investigations were conducted, as a part of the DST sponsored project, to study the seismotectonics of the Bhuj earthquakes affected region. Magnetic total field and vertical field values were collected over the Kutch region with an average station spacing of 5 km. The total field anomaly map reflects NW-SE to WNW-ESE trends with several high amplitude short wavelength anomalies. The analytical signal map of the region has helped in identifying the magnetic sources. They are related to the exposed volcanic and they delineate the subsurface extension of the trap flows. The flow path of induced currents inferred from the nature of transient geomagnetic variations recorded by 10-station magnetometer array suggests presence of blocked crustal structures within the Kutch main land, marked by large lateral conductivity contrast. The long period magnetotelluric measurements in the period range of l0s - 16000s have shown evidence of a crustal conductor in the depth range of 10-17 kin, and a possible lithosphere - asthenosphere boundary at 150 km. It is interesting to note that recent Bhuj earthquake with focus at 17 km depth was seated at the base of this high conductivity layer. First look on the GPS data do not suggest any significant short-term post seismic deformation, following the Bhuj earthquake of 26th January, 2001. GPS repeat measurements are in progress to monitor long-term crustal movements.
Keywords: Bhuj earthquake; Earthquake